Marketisation and privatisation in criminal justice - Albertson, Kevin; Corcoran, Mary; Phillips, Jake (Policy Press, 2020)
As marketisation and privatisation reshape the criminal justice system, this illuminating overview sets out their causes, scale and impacts. With case studies and economic, sociological and criminological perspectives, leading academics consider the evolving roles of public, private and voluntary sectors and possible future reforms.